DEVELOPMENT OF SPEECH ABILITIES OF JUNIORS OF SCHOOLCHILDREN IN THEATER AND GAME ACTIVITIES - I.A. Kravtsova (Academy of Cognitive and Natural Sciences, 2022)
Content, structure, diagnostics, and methodics of the work on development o f theatrical \ actor skills in preschool children is exposed to theoretical and experimental study.